Dynamics of Land Use and Land Cover Changes and Their Impact on Surface Temperature in Domkal Block, West Bengal, India (Iraqi National Journal of Earth Science (INJES), 2026)
Land is increasingly under pressure to meet the demands of a rapidly expanding population, so more resources are needed to maintain basic services and a high standard of living. This pressure leads to the reduction of natural vegetation and the formation of urban heat islands, a global concern linked to rising land surface temperatures, which, in turn, promotes unsustainable development. As a result, understanding the impact of land-use and land-cover changes (LULCC) on ecosystem sustainability has become critical in global change studies. This study utilizes Landsat satellite imagery processed with ArcGIS 10.5 and FRAGSTATS 4.2 to assess changes in land use and land cover, land fragmentation, and their relationship with land surface temperature (LST) and the normalized difference vegetation index (NDVI) in the Domkal block of Murshidabad District. The study assesses the magnitude and direction of these changes between 1991 and 2021 using change vector analysis. The findings reveal significant reductions in agricultural land (80.77 km²) and plantation areas (11.03 km²), offset by increases in built-up land (19.86 km²) and aquatic bodies (1.6 km²). Analysis of land surface temperature indicates an increase from 17-23°C in 1991 to 18-26°C in 2021. These changes are driven by demographic pressures, economic transformations, and reduced agricultural subsidies. The study emphasizes the need for sustainable land management practices, including the conservation of agricultural lands, efficient urban planning, and the implementation of conservation strategies to ensure ecological balance and promote socio-economic development.
Keywords: Land use; Land cover; Land Surface Temperature; Urban Heat Island; Sustainability; Landscape Fragmentation